2016
DOI: 10.1039/c5dt04042f
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of BODIPY-clickate based Hg2+ sensors: the effect of triazole binding mode with Hg2+ on signal transduction

Abstract: BODIPY-clickates, F1 and F2, for the detection of Hg(2+) have been designed, synthesized and characterized. Both F1 and F2 showed hyperchromic shifts in the UV-visible spectra in response to increasing Hg(2+) concentrations. Hg(2+) ion binding caused perturbation of the emission quenching process and chelation induced enhanced bathochromic emission of F1 and F2 to 620 nm and 660 nm, respectively. Job's plot clearly indicated that the binding ratio of F1 and F2 with Hg(2+) was 1 : 1. The NMR titration of BODIPY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Mercury ion (Hg 2+ ) is the most toxic and dangerous contamination, which exists in the form of inorganic salt or organic mercury compound in the food chain. It has high capability of coordination with sulfhydryl groups in biological systems, and has harmful effects on biological systems, which can result in many diseases and even death . Considering that the potential impact of Cu 2+ and Hg 2+ ions can threaten human health and the environment, the development of highly sensitive and selective chemosensors, which can detect and estimate trace levels of Cu 2+ and Hg 2+ ions, is very essential.…”
Section: Introductionmentioning
confidence: 99%
“…Mercury ion (Hg 2+ ) is the most toxic and dangerous contamination, which exists in the form of inorganic salt or organic mercury compound in the food chain. It has high capability of coordination with sulfhydryl groups in biological systems, and has harmful effects on biological systems, which can result in many diseases and even death . Considering that the potential impact of Cu 2+ and Hg 2+ ions can threaten human health and the environment, the development of highly sensitive and selective chemosensors, which can detect and estimate trace levels of Cu 2+ and Hg 2+ ions, is very essential.…”
Section: Introductionmentioning
confidence: 99%
“…Ojida et al developed the BODIPY metal complex for imaging neurofibrillary tangles . We recently reported a BODIPY‐based Hg 2+ sensor that operates on a TICT mechanism with a large Stokes shift . Furthermore, we optimized the method for the synthesis of styryl–BODIPY derivative microwave‐assisted Knoevenegal condensation .…”
Section: Introductionmentioning
confidence: 99%
“…[9] We recently reported a BODIPY-based Hg 2+ sensor that operates on a TICT mechanism with a large Stokes shift. [10] Furthermore, we optimized the method for the synthesis of styryl-BODIPY derivative microwave-assisted Knoevenegal condensation. [11] Here, we report the preparation and characterization of the quinoxaline and anisyl appended BODIPYbovine serum albumin (BSA) complex, which has the potential to be used to identify kinase enzymes qualitatively.…”
Section: Introductionmentioning
confidence: 99%
“…5 Vedamalai et al reported on a BODIPY-clickate based fluorescence probe. 6 These developed compounds were applied to determine Hg 2+ not only in aqueous water but also for imaging of living cells. 5,6 A specific T-Hg-T mismatch on DNA was also applied to the fluorometric detection of Hg.…”
Section: +mentioning
confidence: 99%
“…6 These developed compounds were applied to determine Hg 2+ not only in aqueous water but also for imaging of living cells. 5,6 A specific T-Hg-T mismatch on DNA was also applied to the fluorometric detection of Hg. Zhang et al used N-methyl mesoporphylin IX (NMM)/G-quadruplex DNA system as reporter.…”
Section: +mentioning
confidence: 99%